University Students' Perception on the Verbal Interaction through WhatsApp Chat Group - Sujarwo Sujarwo; Sukmawati Sukmawati; Asdar Asdar; Suharti Siradjuddin; Nina Ariani (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
Verbal interactions will occur when both the teacher/lecturer and learners could completely understand what each other means. It happens verbally among the teacher and learners during the teaching learning activity (Mardiana et al., 2019). This study was mainly conducted to examine the University students’ perception on verbal interaction through WhatsApp chat group. This study used qualitative descriptive method was used to achieve the objective of this study. Observation and a questionnaire were adopted as tools for data collection. A total number of samples was 14 English as a Foreign Language learners in university students. The analysis of the data revealed that university students’ perception on verbal interaction gave the positive feedback towards WhatsApp chat group. This proves that ordinarily learners selected agree with utilizing WhatsApp chat group in doing verbal interaction. Hence, utilizing of WhatsApp chat group can be recommended as an efficient technique in verbal interaction for teaching and learning process.